2022
DOI: 10.3390/ijms232012236
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Cholesterol, Oxysterols, and Cholesterol Lowering Dietary Compounds on the Immune System

Abstract: Cholesterol and its oxidized forms, oxysterols, are ingested from foods and are synthesized de novo. Cholesterol and oxysterols influence molecular and cellular events and subsequent biological responses of immune cells. The amount of dietary cholesterol influence on the levels of LDL cholesterol and blood oxysterols plays a significant role in the induction of pro-inflammatory state in immune cells, leading to inflammatory disorders, including cardiovascular disease. Cholesterol and oxysterols synthesized de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 209 publications
0
7
0
Order By: Relevance
“…According to the subgroup results, TC decreased in doses of less than 30 g/d and intervention durations of more than 8 weeks. It is plausible that COS higher than 30 g/d can lead to an increase in the percentage of energy intake, as a previous study demonstrated that ALA intake higher than eight g/d increased energy intake and consequently increased the risk of metabolic syndrome [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the subgroup results, TC decreased in doses of less than 30 g/d and intervention durations of more than 8 weeks. It is plausible that COS higher than 30 g/d can lead to an increase in the percentage of energy intake, as a previous study demonstrated that ALA intake higher than eight g/d increased energy intake and consequently increased the risk of metabolic syndrome [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…At high cholesterol levels, the conformational change of SCAP allows itself to interact with insulininduced gene 1 protein (INSIG1) directly and form SCAP/INSIG1 complex, which remains on the endoplasmic reticulum (ER) membrane in an inactive state [37]. At this time, 25-OHC can bind to SREBP-2 and then target either SCAP or INSIG1 to form SREBP-2/SCAP/INSIG1 complex [38]. The formation of SREBP-2/SCAP/INSIG1 complex in mice is dependent on the embedment of 25-OHC into the molecular structure of SCAP/INSIG1 complex and inhibits the transcriptional activity of SREBP-2 and inflammasome assembly [38,39].…”
Section: Inflammasome-mediated Cascadesmentioning
confidence: 99%
“…At this time, 25-OHC can bind to SREBP-2 and then target either SCAP or INSIG1 to form SREBP-2/SCAP/INSIG1 complex [38]. The formation of SREBP-2/SCAP/INSIG1 complex in mice is dependent on the embedment of 25-OHC into the molecular structure of SCAP/INSIG1 complex and inhibits the transcriptional activity of SREBP-2 and inflammasome assembly [38,39]. Furthermore, 25-OHC produced in the LPS-activated mouse MUs is able to successively suppress SREBP-2 activation, cholesterol synthesis, AIM2 inflammasome activity, IL-1β release, and inflammation [33,35,36,[38][39][40].…”
Section: Inflammasome-mediated Cascadesmentioning
confidence: 99%
See 2 more Smart Citations